Low-Cost Microwave-Assisted Partial Pseudomorphic Transformation of Biogenic Silica - Schneider, Denise; Kircheis, Ralf; Wassersleben, Susan; Einicke, Wolf-Dietrich; Gläser, Roger; Enke, Dirk (Frontiers in Chemistry, 2019)
This work introduces a cost and time efficient procedure to specifically increase mesopore volume and specific surface area of biogenic silica (specific surface area: 147 m2 g-1 and mesopore volume: 0.23 cm3 g-1) to make it suitable for applications in adsorption or as catalyst support. The target values were a specific surface area of ~ 500 m2 g-1 and a mesopore volume of ~ 0.40 - 0.50 cm3 g-1. The applied process of partial pseudomorphic transformation was carried out as a single reaction step in a microwave reactor instead of commonly used convective heating. In addition, the conventionally used surfactant cetyltrimethylammonium bromide (CTABr) was substituted by the low-cost surfactant (Arquad® 16-29, aqueous cetyltrimethylammonium chloride (CTACl) solution). The influence of microwave heating, type of surfactant as well as the concentration of NaOH and CTACl on the textural and structural properties of the modified biogenic silica was investigated using nitrogen adsorption as well as scanning and transmission electron microscopy. The results show that the textural parameters of the modified biogenic silica can be exactly controlled by the amount of NaOH in the reaction solution. By variation of the NaOH concentration, specific surface areas in the range of 215 - 1001 m2 g-1 and mesopore volumes of 0.25 - 0.56 cm3 g-1 were achieved after reaction at 393 K for 10 min. The presented microwave route using the low-cost surfactant solution decreases the reaction time by 99 % and as shown in an example for German prices, lowers the costs for the surfactant by 76 - 99 %.